Análise experimental e modelagem de motor de combustão interna operando com etanol super-hidratado - Ambrós, Weslei Monteiro (2013)
The use of ethanol as fuel has encouraged many countries to improve their production for this purpose. However, costs relating to their current production model have been occasionally mentioned as a drawback to its use. Among these stands out costs the energy expenditure necessary for distillation of the wort, which creates a final product with approximate composition of 95% by volume of ethanol in water. An alternative to disposal cost of this would be the use of ethanol with high water content (above 5% by volume). With this in mind, this study aims to develop a mathematical model that, together with experimental data, assess the effect that the use of alcohol fuel blends super hydrated has on the performance of spark ignition engines. For this, together with the commercial hydrous ethanol, blends were prepared with volume fractions of 90% (E90W10), 80% (E80W20), 70% (E70W30) and 60% (E60W40) ethanol in water and tests conducted in which maintained the ignition point and the fixed point which is advanced to obtain the maximum brake torque (MBT). The model has presented a good agreement wich pressure gradients and temperature in the cylinder and predicted changes in power, torque, efficiency and specific consumption of ethanol with relative errors less than 7%. For the variations in the test conditions the relative error was less than 13%. However, improvements must be made to calculate the mass of water in the mixture. The specific consumption of the mixture gradually increased with water content on the blend. Among fuels tested, E70W30 exhibited the best performance, followed by E80W20, both of which had higher yields than the commercial ethanol.